Farm-like indoor microbiota in non-farm homes protects children from asthma development - Kirjavainen, Pirkka V. (Nat Med, 2019)
Asthma prevalence has increased in epidemic proportions with urbanization, but growing up on traditional farms offers protection even today.1 The asthma-protective effect in farms appears to be associated with rich home dust microbiota,2,3 which could be used to model a health-promoting indoor microbiome. Here we show by modelling differences in house dust microbiota composition between farm and non-farm homes of Finnish birth cohorts4 that in children who grow up in non-farm homes asthma risk decreases as the similarity of their home bacterial microbiota composition to that of farm homes increases. The protective microbiota had a low abundance of Streptococcaceae relative to outdoor-associated bacterial taxa. The protective effect was independent of richness and total bacterial load and was associated with reduced proinflammatory cytokine responses against bacterial cell wall components ex vivo. We were able to reproduce these findings in a study among rural German children2 and showed that children living in German non-farm homes with an indoor microbiota more similar to Finnish farm homes have decreased asthma risk. The indoor dust microbiota composition appears as a definable, reproducible predictor of asthma risk and a potential modifiable target for asthma prevention.